Das Verhältnis von Arbeit und Welt: Hannah Arendt, Emanuel Levinas, Eugen Fink und Donna J. Haraway im Polylog - Schmitz, Vanessa (HannahArendt.net, 2025)
As ambiguous as the understanding of the world and of work are, the answers to their relationship to each other are just as contradictory. If both are in a foundational relationship with our reality, they address the development of the human being in its existential dimension, insofar as it is about nothing more and nothing less than our concrete life.Whether world and work are understood as opposing or mutually underpinning dimensions is just as important for our human coexistence and the web of concrete life in an all-encompassing sense as the location of work in the individual and/or intersubjective sphere. Arendt's, Levinas', Fink's and Haraway's approaches are positioned in this respect in order to pursue the question of the effectiveness of work, to discover the many facets of work and thus ultimately to explore a horizon of possibilities for us.